Features of “All LNA” Duplexes Showing a New Type of Nucleic Acid Geometry - Charlotte Förster; André Eichert; Dominik Oberthür; Christian Betzel; Reinhard Geßner; Andreas Nitsche; Jens P. Fürste (Journal of Nucleic Acids)
“Locked nucleic acids” (LNAs) belong to the backbone-modified nucleic acid family. The 2′-O,4′-C-methylene-β-D-ribofuranose nucleotides are used for single or multiple substitutions in RNA molecules and thereby introduce enhanced bio- and thermostability. This renders LNAs powerful tools for diagnostic and therapeutic applications. RNA molecules maintain the overall canonical A-type conformation upon substitution of single or multiple residues/nucleotides by LNA monomers. The structures of “all” LNA homoduplexes, however, exhibit significant differences in their overall geometry, in particular a decreased twist, roll and propeller twist. This results in a widening of the major groove, a decrease in helical winding, and an enlarged helical pitch. Therefore, the LNA duplex structure can no longer be described as a canonical A-type RNA geometry but can rather be brought into proximity to other backbone-modified nucleic acids, like glycol nucleic acids or peptide nucleic acids. LNA-modified nucleic acids provide thus structural and functional features that may be successfully exploited for future application in biotechnology and drug discovery.